Heat transfer augmentation of triplex type latent heat thermal energy storage using combined eccentricity and longitudinal fin - Patel, Jay R. (Journal of energy storage)
The universe has shifted its focus from non-renewable to renewable energy sources from the last decade. The limited availability of fossil fuels and pollution is the reason behind the utilization of renewable sources. A major renewable energy source, solar energy, requires efficient thermal energy storage due to its intermittent nature. Phase change material (PCM) can store a large amount of heat by changing its phases. However, the low thermal conductivity of PCM makes its usage very limited. Hence, PCM's heat transfer augmentation technique using eccentricity and fin is studied in the present research. First of all, positive (lower displacement of the inner tube) and negative eccentricity (upper displacement of the inner tube) are studied in triplex type latent heat thermal energy storage (TTLHTES). Among the eccentricities of-15 mm to +15 mm, the eccentricity of +10 mm is found most effective in melting with a 27.63% reduction in melting time, while-3 mm eccentricity is found most effective in solidification with a 12.82% reduction in solidification time. The combination of fins with eccentricity is examined for melting and solidification enhancement. The combination of fin and eccentricity efficiently reduces melting time, with a maximum decrement of 67.37% with +3 mm eccentric TTLHTES with four fins. However, the only fin without any eccentricity is found more effective in solidification enhancement. The solidification time is reduced maximum by 46.15% using four longitudinal fins and no eccentricity. It can be concluded that fin and eccentricity must be coupled when melting time is required to enhance. However, only fin must be utilized when solidification is more critical.